Sedation with Combination of Midazolam, Pentazocine and Propofol for Colonoscopy in Outdoor Patients - KC, Nagendra Bahadur; Pokhrel, Dinesh (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Diagnostic colonoscopies are generally done in OPD basis and requires sedation and analgesia to relieve both anxiety and pain. Propofol and midazolam combination is used worldwide and allows rapid and profound sedation with quick recovery. But data on combined sedation with midazolam, pentazocine and propofol are not found. So this study was conducted to test this combination for day care surgery. Methods: Prospectively, 242 colonoscopy procedures who had received combined sedation with midazolam, pentazocine and propofol were analysed. Midazolam and Pentazocine were given intravenously as a single dose of 2 mg and 15 mg respectively. 20 mg of Propofol was given bolus, than 10 mg top up titrating sedation till procedure is finished. Pulse, Non Invasive Blood pressure and oxygen saturation were recorded. Patients' genders, ages, weight, length of procedure and the need of total received Propofol for complete sedation in mg were recorded. Movement during procedure, the time of recovery and any complications were also recorded. Patients were also asked whether they had any memories of procedure. Results: Lower dose of propofol is required to produce adequate aesthesia. There are no complication and vitals were stable including oxygen Saturation. There was quicker recovery as all patients responds on verbal command just after the procedure and no patient had memories of the procedure. All patients safely discharged within one hour. Conclusions: The combination is safe and comfortable for patients undergoing diagnostic colonoscopy to produce adequate anaesthesia without any significant complications. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/7-9 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7900